Reforming Regional-Local Finance in Russia - Martinez-Vazquez, Jorge; Timofeev, Andrey; Boex, Jameson (Washington, DC: World Bank, 2012)
The book assesses the current state of Russia's regional and local fiscal relations, and self-government, and analyzes the related reforms undertaken over the past decade. The analysis is based on the kind of first-hand experience and in-depth knowledge of Russian intergovernmental reforms that only a handful of Western scholars possess. This book complements the earlier World Bank Institute (WBI) title Russia's Transition to a New Federalism (2001), reflecting the shift in Russia's policy reform agenda, from an emphasis on federal and regional relations, to the regional and local levels. The study uses a framework that integrates all the building blocks of federalism: size and structure of jurisdictions, expenditures, revenues, transfers, and borrowing. It offers reform options based on international practices and normative principles, while also identifying some dangers that may arise in implementing the next round of proposed intergovernmental reforms in Russia. The book was prepared as part of the WBI's program to train central and local government officials to carry out intergovernmental reforms, and to build a core group of local trainers who can deliver future programs independently. The current approach of the federal government toward regional-local relations presents a mix of rigid norms and loose guidelines. The Constitution gives the federal and regional government joint responsibility for the implementation of the citizens' right to local self-government. This has enabled the federal government to pass a number of constitutional laws that develop the framework for local governance. Regional governments were supposed to establish the system of local self-government on their territory in accordance with federal legislation, by passing regional legislation that would further elaborate the regional-local government arrangements. However, in areas where regional governments had some degree of policy freedom, often many did not have the required technical expertise to make their own informed policy choices. The easiest solution for defining regional-local relations seems to have been to copy the federal approach to federal-regional relations, and apply it at the regional-local level.